Effect Of Led Light Source Variation Toward Curly Lettuce (Lactuca sativa Var. Crispa L) Growth And Yield In - Antonius Novinanto; Andree Wijaya Setiawan (Agric, 2019)
In conventional curly lettuce cultivation there are several obstacles such as altitude, temperature, humidity, nutrient availability and light intensity that caused lettuce can not grow optimally. Indoor cultivation is one way to overcome problems that occurred in conventional cultivation, one of which is the intensity of light that is not suitable for the growth of lettuce plants. This study aims to determine the optimal LED electrical power and the effect of white LED lights and grow light on growth of lettuce plants with floating raft hydroponic cultivation system. This research has been carried out at Satya Wacana Christian University’s Faculty of Agriculture and Business seed laboratory. The study used a randomized block design with six treatments: 100 watt grow light; 200 watt grow light; 300 watt grow light; 100 watt white light; 200 watt white light; 300 watt white light, which will be repeated four times. Parameters to be measured include the number of leaves, canopy diameter, crown wet weight, root wet weight, chlorophyll b, total chlorophyll and leaf area. Light intensity treatment carried out with a box with a size of 1x1 m placed in a dark room. The results showed that the 300 watt grow light treatment gave the best results, with canopy diameter (45.10 cm), number of leaves (18.25 strands), canopy wet weight (225,967 g), heavy dry canopy weight (9.90 g), canopy dry weight (4.75 g), and leaf area 6195,378 (mm).